Studi Deskriptif Terkait Pemahaman Mahasiswa Hukum Terhadap Tindakan Plagiarisme - Ni Made Anggi Arlina Putri; Evi Faridawaty (IAHN Tampung Penyang Palangka Raya, 2022)
This study aims to describe the understanding of law students regarding plagiarism behavior. The form of this research is descriptive quantitative research. Data was collected through an online questionnaire distributed to 45 students of the Dharma Sastra Faculty using a google form. From the results of the data analysis, it is known that students' understanding can be said to be good with the respondents answering the questionnaire as a whole. Based on the data from the survey that has been conducted, it was found that all aspects studied were in the range of values ​​from 3.40 to 4.20. It can be interpreted that students have a good understanding of plagiarism. In this study, there were four (4) categories that were examined to get conclusions about students' understanding of plagiarism. For the category of student understanding of plagiarism behavior is at a score of 3.9. This value can be interpreted that students can determine the behavior that is said to be plagiarism. For the second category, namely the ability of students to classify plagiarism behavior, the score is 3.51. This means that students have a good understanding in classifying plagiarism behavior. The third category, good and correct quoting methods, got a score of 3.96, namely students have good knowledge of how to cite properly and correctly. For the last category, namely the category of understanding about violations of plagiarism, the data shows a value of 3.76 which means that students of the Faculty of Dharma Sastra have a good understanding of violations of plagiarism behavior. However, there are still acts of plagiarism that are carried out intentionally or unintentionally by students in completing coursework, so we give an appeal to all elements of leadership, especially in the Dharma Sastra Faculty, so that they can set limits on writing ethics, editing and others. In addition, it is necessary to socialize writing ethics so that students get qualified information and knowledge in writing scientific articles/papers.